Bāp ke ḵẖat̤ beṭī ke nām : jin meṉ zamīn aur dunyā ke banne, jānvaroṉ aur ādmīyoṉ ke paidā hone, basne aur baṛhne kā ḥāl baccoṉ ko batlāyā gayā hai - Nehru, Jawaharlal, 1889-1964 (SAMP early 20th-century Indian books project, 1935)
Translation of a collection of letters from Jawaharlal Nehru to his young daughter, Indira Gandhi, dealing with the beginning of the earth, man's awareness of himself, and the history and civilization of the ancient world.